2(z-1)=5(z+8)-15

Simple and best practice solution for 2(z-1)=5(z+8)-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(z-1)=5(z+8)-15 equation:


Simplifying
2(z + -1) = 5(z + 8) + -15

Reorder the terms:
2(-1 + z) = 5(z + 8) + -15
(-1 * 2 + z * 2) = 5(z + 8) + -15
(-2 + 2z) = 5(z + 8) + -15

Reorder the terms:
-2 + 2z = 5(8 + z) + -15
-2 + 2z = (8 * 5 + z * 5) + -15
-2 + 2z = (40 + 5z) + -15

Reorder the terms:
-2 + 2z = 40 + -15 + 5z

Combine like terms: 40 + -15 = 25
-2 + 2z = 25 + 5z

Solving
-2 + 2z = 25 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-2 + 2z + -5z = 25 + 5z + -5z

Combine like terms: 2z + -5z = -3z
-2 + -3z = 25 + 5z + -5z

Combine like terms: 5z + -5z = 0
-2 + -3z = 25 + 0
-2 + -3z = 25

Add '2' to each side of the equation.
-2 + 2 + -3z = 25 + 2

Combine like terms: -2 + 2 = 0
0 + -3z = 25 + 2
-3z = 25 + 2

Combine like terms: 25 + 2 = 27
-3z = 27

Divide each side by '-3'.
z = -9

Simplifying
z = -9

See similar equations:

| (5u+4)(9-u)=0 | | -3(1x+2)=-21 | | 7x^2-40x=2x^2-5x | | 59=6x+x+10 | | (11x+3)+(6x-5)= | | 3*5xytu=5 | | 3xy=8x | | n^2+n=4n | | (12x^2+6x-6)-(12x^2+9x+3)= | | -4s+6t=5 | | -x+6+4x=-21 | | xyz=27 | | 70-10(4x+6)=40 | | ghj=9 | | 10000000000=2x | | -2x^2-22=0 | | 4-21=9x-5-8x | | (8+u)(5u+1)=0 | | 165.832=10.91 | | 0.500=(x+12.00/2)3.60 | | 55+2x+x-10=180 | | 5(4x+2)=15 | | 3/5x-6=12 | | 2secant+3=-1 | | 4(3y-7)=16 | | 6(14x+18)=-30 | | n(n+1)=2 | | 7x-6x+13=10-5 | | 2sec+3=-1 | | x=0+2(-9.81)(-32.4) | | 2/5x+1=3+3/10 | | 180x^2+35x-180=0 |

Equations solver categories